Captura de CO2 em estruturas metalorgânicas com sítios metálicos abertos impregnadas com líquidos iônicos - Oliveira, Leon Torres de (2020)
This study presents results obtained from molecular simulation to analyze the effects of impregnation of metal-organic structures with ionic liquids to improve carbon dioxide capture and selectivity. The effect of the impregnation at the adsorptive sites, particularly those present near the metal clusters, is analyzed from the radial density function. The ionic liquids [Bmim+][PF6-] and [Bmim+][SCN-] were chosen for this paper, and considerable improvements were detected in the uptake with 15 and 25% wt. of [Bmim+][SCN-] at the structures, with values doubling at pressures below 200 kPa. Mixtures of CO2-CH4 (30:70 ratio) and CO2-N2 (15:85 ratio) were studied to tailor this study to the application in CO2 capture for combustion gases (flue gas) and natural gas. The results obtained make it evident that the characteristics added by the impregnation by ionic liquids have potential for the application in the capture of CO2.